Is the Kok effect a respiratory phenomenon? Metabolic insight using 13C labeling in Helianthus annuus leaves. Issue 4 (21st July 2020) - Gauthier, Paul P. G.; Saenz, Natalie; Griffin, Kevin L.; Way, Danielle; Tcherkez, Guillaume
Summary: The Kok effect is a well‐known phenomenon in which the quantum yield of photosynthesis changes abruptly at low light. This effect has often been interpreted as a shift in leaf respiratory metabolism and thus used widely to measure day respiration. However, there is still no formal evidence that the Kok effect has a respiratory origin. Here, both gas exchange and isotopic labeling were carried out on sunflower leaves, using glucose that was 13 C‐enriched at specific C‐atom positions. Position‐specific decarboxylation measurements and NMR analysis of metabolites were used to trace the fate of C‐atoms in metabolism. Decarboxylation rates were significant at low light (including above the Kok break point) and increased with decreasing irradiance below 100 µmol photons m −2  s −1 . The variation in several metabolite pools such as malate, fumarate or citrate, and flux calculations suggest the involvement of several decarboxylating pathways in the Kok effect, including the malic enzyme. Our results show that day respiratory CO2 evolution plays an important role in the Kok effect. However, the increase in the apparent quantum yield of photosynthesis below the Kok break point is also probably related to malate metabolism, which participates in maintaining photosynthetic linear electron flow.